So close and yet so far away: long‐distance dispersal events govern bryophyte metacommunity reassembly. (8th August 2016) - Barbé, Marion; Fenton, Nicole J.; Bergeron, Yves
Summary: Metapopulation dynamics have been used to explain bryophyte dispersal patterns and they predict that population abundances vary with the spatial distribution of habitat and with species traits. However, results from stand and landscape studies are contradictory as both distance‐dependent and distance‐independent patterns have been found. These studies have typically included only a few species, which limits interspecies comparison. It is the time to investigate bryophyte dispersal at the metacommunity scale. We studied bryophyte dispersal patterns in a system made up of burned matrices containing unburned residual forest patches. The importance of short‐ versus long‐distance dispersal was examined by comparing extant and propagule rain communities in residual forest patches of three fire sites using both species and life strategies. Extant and propagule rain communities were distinct. Several propagule rain species, of all life strategies, did not originate from the closest extant community, suggesting that regional dispersal events are important, following the inverse isolation hypothesis. Temporal, spatial and structural characteristics of the environment had a greater influence on dispersal than distance, which only influenced similarity patterns at the regional scale, highlighting the importance of propagule source attributes for the conservation of bryophyte metacommunities. Synthesis . Long‐distance dispersal may be the rule and not the exception in bryophyte metacommunities. Therefore, bryophyte metacommunity dynamics depend on several dispersal scales, and residual forest patches can contribute both to local and regional diaspore clouds. Species' environmental tolerance during establishment and their ability to produce copious amounts of spores may be more important filters in bryophyte metacommunity dynamics than dispersal distance. Abstract : Long‐distance dispersal may be the rule and not the exception in bryophyte metacommunities. Therefore, bryophyte metacommunity dynamics depend on several dispersal scales, and residual forest patches can contribute both to local and regional diaspore clouds. Species' environmental tolerance during establishment and their ability to produce copious amounts of spores may be more important filters in bryophyte metacommunity dynamics than dispersal distance.